Navigating stem cell culture: insights, techniques, challenges, and prospects - Górska, Aleksandra; Trubalski, Mateusz; Borowski, Bartosz; Brachet, Adam; Szymańczyk, Sylwia; Markiewicz, Renata (Frontiers in Cell and Developmental Biology, 2024)
Stem cell research holds huge promise for regenerative medicine and disease modeling, making the understanding and optimization of stem cell culture a critical aspect of advancing these therapeutic applications. This comprehensive review provides an in-depth overview of stem cell culture, including general information, contemporary techniques, encountered problems, and future perspectives. The article begins by explaining the fundamental characteristics of various stem cell types, elucidating the importance of proper culture conditions in maintaining pluripotency or lineage commitment. A detailed exploration of established culture techniques sheds light on the evolving landscape of stem cell culture methodologies. Common challenges such as genetic stability, heterogeneity, and differentiation efficiency are thoroughly discussed, with insights into cutting-edge strategies and technologies aimed at addressing these hurdles. Moreover, the article delves into the impact of substrate materials, culture media components, and biophysical cues on stem cell behavior, emphasizing the intricate interplay between the microenvironment and cell fate decisions. As stem cell research advances, ethical considerations and regulatory frameworks become increasingly important, prompting a critical examination of these aspects in the context of culture practices. Lastly, the article explores emerging perspectives, including the integration of artificial intelligence and machine learning in optimizing culture conditions, and the potential applications of stem cell-derived products in personalized medicine. This comprehensive overview aims to serve as a valuable resource for researchers and clinicians, fostering a deeper understanding of stem cell culture and its key role in advancing regenerative medicine and biomedical research.